On the Concepts of Virtual “Things” and “Thing-ness” - A. M. Doiev (Цифровое право, 2024)
As a result of technological progress, established traditional legal concepts require constant refi nement to permit their optimal regulation. For example, virtual (digital) “things” — or tokens (NFTs) — are subject to disputes concerning whether it is preferable to rely on a traditional legal institution (e.g., property and intellectual property) or create a completely new regime “from scratch”. Using historical and comparative legal methods based on doctrinal sources, the present work explores the concepts of thing and property in the common law of nation states. The closest functional analogues in the civil law systems the res (“thing”) and in rem (“right”) are compared. Common law in rem rights are established to have emerged in the Middle Ages in form of the feudal system of different statuses with respect to land (estates). Later, under the infl uence of Wesley Hohfeld’s research on legal opposites and correlatives, this system was substantially modernized through the deconstruction of property into a “bundle of rights”. An analysis of a published translation of Joshua Fairfi eld’s article convincingly demonstrates that cryptocurrency, just as any token, is indistinguishable in its principal aspects from a “thing” in the civil-law sense. A similar conclusion is reached in the context of Russian law: the main criteria of “thingness” — materiality and the possibility of being the object of exclusive possession — are equally fulfi lled when it comes to tokens, land plots or chairs in one’s apartment. Accordingly, intuitive notions about things as products having real nature are obviously outdated and should be replaced with a jurisprudential understanding of the “thing” as a result of social interaction, rather than having a certain nature in and of itself. The important functions of materiality consist in a reduction of information costs for participants in legal relations due to the natural formation of intuitive expectations, as well as prejudices about the scope and characteristics of these rights.